Evaluation of immunomodulatory potential of probiotic conditioned medium on murine macrophages - Mohammad A. A. Al-Najjar; Shaymaa B. Abdulrazzaq; Lujain F. Alzaghari; Asma Ismail Mahmod; Amin Omar; Eliza Hasen; Tamara Athamneh; Wamidh H. Talib; Dinesh Kumar Chellappan; Muna Barakat (Scientific Reports, 2024)
Abstract Probiotics are a mixture of beneficial live bacteria and/or yeasts that naturally exist in our bodies. Recently, numerous studies have focused on the immunostimulatory effects of single-species or killed multi-species probiotic conditioned mediums on macrophages. This study investigates the immunostimulatory effect of commercially available active, multi-species probiotic conditioned medium (CM) on RAW264.7 murine macrophages. The probiotic CM was prepared by culturing the commercially available probiotic in a cell-culture medium overnight at 37 °C, followed by centrifugation and filter-sterilization to be tested on macrophages. The immunostimulatory effect of different dilution percentages (50%, 75%, 100%) of CM was examined using the MTT assay, proinflammatory cytokine (tumor necrosis factor TNF-alpha) production in macrophages, migration, and phagocytosis assays. For all the examined CM ratios, the percentages of cell viability were > 80%. Regarding the migration scratch, TNF-alpha and phagocytosis assays, CM demonstrated a concentration-dependent immunostimulatory effect. However, the undiluted CM (100%) showed a significant (p-value < 0.05) stimulatory effect compared to the positive and negative controls. The findings suggest that the secretions and products of probiotics, as measured in the CM, may be closely associated with their immune-boosting effects. Understanding this relationship between probiotic secretions and immune function is crucial for further exploring the potential benefits of probiotics in enhancing overall health and well-being.